Heart failure development in obesity: underlying risk factors and mechanistic pathways. (24th November 2020) - Jamaly, Shabbar; Carlsson, Lena; Peltonen, Markku; Andersson‐Assarsson, Johanna C.; Karason, Kristjan
Abstract: Aims: People with obesity are at risk for developing heart failure (HF), but little is known about the mechanistic pathways that link obesity with cardiac dysfunction. Methods and results: We included 2030 participants from the Swedish Obese Subjects study who received conventional obesity treatment. First‐time detection of HF was obtained by cross‐checking the study population with the Swedish National Patient Register and the Swedish Cause of Death Register. We also examined if atrial fibrillation and myocardial infarction as time‐dependent variables could predict incident HF The mean age of the study cohort was 48.7 years, and 28% were men. The mean body mass index at baseline was 40.1 kg/m 2 and remained stable during a median follow‐up of 20.1 years. First‐time diagnosis of HF occurred in 266 of patients and was related to male sex, increasing age, greater waist–hip ratio, hypertension, higher cholesterol, diabetes mellitus, and elevated free thyroxine in univariable analysis. Estimated glomerular filtration rate was negatively related to HF risk. In multivariable analysis, atrial fibrillation, which is related to HF with preserved ejection fraction (HFpEF), and myocardial infarction, which is linked to HF with reduced ejection fraction (HFrEF), were strongly associated with incident HF with sub‐hazard ratios 3.75 (95% confidence interval: 2.72–5.18, P < 0.001) and 3.68 (95% confidence interval: 2.55–5.30, P < 0.001), respectively. Conclusions: Both atrial fibrillation and myocardial infarction as time‐dependent variables were independently and strongly related to incident HF in people with excess body fat, suggesting two main obesity‐related mechanistic pathways leading to either HFpEF or HFrEF.